Effects of the crude and the n-hexane extract of Nigella sativa Linn.(kalajira) upon diabetic rats - Khanam, Matira; Dewan, Zesmin Fauzia (Bangladesh Journal of Pharmacology, 2008)
The study was carried out to investigate into the effect of concomitant administration of the crude and the n-hexane extract of Nigella sativa (kalajira) upon streptozotocin-induced diabetic adult male rats. Diabetes was induced by a single intraperitoneal injection of streptozotocin on day 1 while crude nigella powder in deionized water and the n-hexane extract of nigella were administered orally concomitantly from day 1 to 21. Rats were sacrificed on day 22. The serum glucose and cholesterol concentrations that were elevated in diabetic rats were normalized or near normalized by the crude nigella or the n-hexane extract administration; while the elevated serum triglyceride concentrations of the diabetic rats were brought down to lower than control values. The pancreatic GSH was closer to control value, and pancreatic histology suggested reappearance of Î² cells. The crude nigella concomitant to streptozotocin (STZ + Nc) administration appeared to provide better alleviation compared to the n-hexane extract of nigella concomitant to streptozotocin (STZ + H) administration.